2007
DOI: 10.1093/aje/kwm064
|View full text |Cite
|
Sign up to set email alerts
|

Motor Vehicle Crash Injury Rates by Mode of Travel, United States: Using Exposure-Based Methods to Quantify Differences

Abstract: The authors used traffic exposure data to calculate exposure-based fatal and nonfatal traffic injury rates in the United States. Nationally representative data were used to identify fatal and nonfatal traffic injuries that occurred from 1999 to 2003, and the 2001 National Household Travel Survey was used to estimate traffic exposure (i.e., person-trips). Fatal and nonfatal traffic injury rates per 100 million person-trips were calculated by mode of travel, sex, and age group. The overall fatal traffic injury r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
0
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(176 citation statements)
references
References 33 publications
7
156
0
13
Order By: Relevance
“…Logistic regression modeling was used to compute the likelihood of an injury versus impact severity. Several predictor variables that have been identified as influencing injury risk were included, such as total delta-V (Kononen et al 2011;Kusano and Gabler 2012), seat belt use (Durbin et al 2003(Durbin et al , 2005, driver age (Langford and Koppel 2006;McCoy et al 1989), driver gender (Beck et al 2007;Mock et al 2002;Yau 2004), and whether or not the vehicle was equipped with side airbags (Arbelaez et al 2002;Kuppa et al 2003). The computation for calculating system effectiveness (i.e., the proportion of intersection crashes/injuries that could have potentially been prevented) can be found in the Appendix.…”
Section: Injury Benefits Estimatesmentioning
confidence: 99%
“…Logistic regression modeling was used to compute the likelihood of an injury versus impact severity. Several predictor variables that have been identified as influencing injury risk were included, such as total delta-V (Kononen et al 2011;Kusano and Gabler 2012), seat belt use (Durbin et al 2003(Durbin et al , 2005, driver age (Langford and Koppel 2006;McCoy et al 1989), driver gender (Beck et al 2007;Mock et al 2002;Yau 2004), and whether or not the vehicle was equipped with side airbags (Arbelaez et al 2002;Kuppa et al 2003). The computation for calculating system effectiveness (i.e., the proportion of intersection crashes/injuries that could have potentially been prevented) can be found in the Appendix.…”
Section: Injury Benefits Estimatesmentioning
confidence: 99%
“…In this context, Beck et al (2007) have found that, relative to passenger vehicle occupants, bicyclists and pedestrians in the U.S. are 2.3 and 1.5 times, respectively, more likely to be fatally injured on a given trip.…”
mentioning
confidence: 99%
“…In addition to this, the impact of comfort and safety provided by rapid rail transit systems should be evaluated within the cost-benefit evaluation framework. Public rail transit is relatively safe mode compared to car-based transportation considering that rail transit travel has lower fatality rates than automobile travel [109]. Ewing et al [99] found that traffic fatality rates are lower for the mixed land-use developments that offer alternative modes of transportation compared to those of automobile-oriented sprawled developments.…”
Section: Cba Resultsmentioning
confidence: 99%